Implementation of the Saving Matrix and Nearest Neighbor Methods in Planning Courier Route for Package Distribution in the Kudus Area - Sekarningtyas, Hikmah; Noviana, Eka (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The rapid growth of the courier service industry, triggered by the increasing public demand for fast delivery services, has made it necessary for the Post Office to optimize the distribution process to ensure timely package delivery. The selection of distribution routes is a factor in achieving efficiency and effectiveness of delivery. Currently, the Kudus Post Office serves 9 sub-districts with 129 villages, using 12 couriers to deliver goods. However, the distribution route pattern that has not been well planned, causes a mismatch in delivery time. Thus, this study focuses on the formation of a package distribution route pattern using the Saving Matrix and Nearest Neighbor Methods, in designing a planned courier route pattern. The purpose of this method is to find out the route with the minimum distance, so as to produce an optimal delivery route that can increase customer satisfaction through faster delivery services. The results of this study are the formation of 12 package distribution route patterns for each courier, with a total difference in distance between the savings matrix and nearest neighbor methods of 127.75 km.